ANALISIS PEMBELAJARAN SEJARAH DENGAN PENDEKATAN SCIENTIFIK DALAM KURIKULUN 2013 DI MADRASAH ALIYAH NEGERI KETAPANG KALIMANTAN BARAT - Sadikin, Muhammad; W., Warto; Joebagio, Hermanu (Sebelas Maret University (UNS), 2015)
The aims of this study was to identify and analyze: (1) the planning of teaching history with a scientific approach to the 2013 curriculum at Madrasah AliyahNegeriKetapang in West Borneo; (2) explaining the implementation of the teaching history with a scientific approach to the 2013 curriculum at Madrasah AliyahNegeriketapang West Borneo; (3) how the evaluation of teaching history process with a scientific approach to the 2013 curriculum at Madrasah AliyahNegeriketapang West Borneo (4) describing the obstacles encountered in the teaching of history with a scientific approach to the 2013 curriculum at Madrasah AliyahNegeriketapang West Kalimantan.The result of this research showed (1) in lesson teaching plan, teacher made learingby scientific approach include observing, questioning, experimenting, associating, experimenting device independently to pass the liberation subject teacher’s; (2) the process of learning social studies by scientific include observing, questioning, experimenting, associating, experimenting and to support by three learning theory is learning theory Brunner, learning theory Piaget and learning theory Vygotsky. Learning modelProblem Based Learning (PBL)islearning model relation with scientific approach, make use of is Problem Based Learning (PBL)and get positive influence from teacher and student’s, so that to impact positive towards learning student center; (3) technique the assessment learning social studies by scientific is test and non test, aspect cognitive value with tes, aspectaffectiveandaspect psychomotor value with observation and relation with scientific approach KI-1 assessment (religius) value to overload is observation, KI-2 assessment (social) value to overload is observation, KI-3 (cognitive) value to overload is test and KI-4 (skill) value to overload is test and observation. Technique of assessment test and non test;(4) the efforts to overcome obstacles skill value to overload is observation and test to perform, the teacher cannot maximal together and comprehension minim teacher in scientific approach, cannot to fit between syllabi with student book.